The Implementation of Guided Question Technique in Teaching Writing Recount Text for Senior High School Students (RETAIN, 2017)
The Implementation of Guided Question Technique in Teaching Writing Recount Text for Senior High School Students Vefi Nur Indah Sari English Education, Language and Art Faculty, State University Surabaya indahvefi@gmail.com Nur Chakim, S.Pd., M.Pd. English Education Department, Faculty of Language and Art, State University of Surabaya hakimnur_24@yahoo.com Abstrak Menulis adalah salah satu aspek penting dalam belajar bahasa Inggris karena menulis mengajarkan siswa untuk menghasilkan bahasa dalam bentuk teks. Namun, tidak mudah mengajar menulis. Peneliti menemukan beberapa masalah yang muncul pada pengajaran menulis teks recount. Biasanya siswa kesulitan untuk mengorganisir ide mereka dalam menulis teks. Kemudian, pada umumnya guru tidak memiliki materi yang baik dan tehnik yang sesua. Berdasarkan alas an tersebut, penulis menggunakan tehnik Guided Question yaitu memberikan pertanyaan – pertanyaan sebelum membuat teks. ada tiga hal yang dianalisis: 1) bagaimana penerapan tehnik Guided Question dalam pengajaran menulis teks recount?, 2) Bagaimana komposisi siswa sebagai hasil dari pengajaran menulis teks recount dengan menggunakan tehnik Guided Question?, 3) Bagaimana respon para siswa pada penerapan tehnik Guided Question dalam pengajaran menulis teks recount? Sehubungan dengan pertanyaan – pertanyaan tersebut, penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif. Selain itu, instrumentnya adalah field note, observation checklist, students’ task, dan interview. Penelitian ini diadakan tiga kali observasi di kels X – IPS 3 SMAN 1 Mojosariuntuk mengetahui penerapan tehnik Guided Question dalam pengajaran teks recount untuk siswa sekolah menengah atas. Hasil dari observasi menunjukkan bahwa komposisi siswa pada level baik. Selain itu, pada interview menunjukkan bahwa kebanyakan siswa memberikan respon yang positif. Mereka setuju bahwa tehnik Guided Question membantu dalam mengorganisir ide siswa. Kesimpulannya, tehnik Guided Question dapat menjadi tehnik yang sesuai dalam pengajaran menulis teks recount. Kata Kunci : Menulis, Teks Recount, Teknik Guided Question Abstract Writing is one of important aspects in learning language because it allows the students to produce language in the form of text. Raimes (1983) claimed that writing is not only as a part of second-language syllabus but also as a medium to help students learning language. Yet, teaching writing is not easy. The researcher found some problems which occurred in teaching writing recount text. The students were difficult to organize their ideas. Moreover, the teacher generally did not have good material and appropriate technique. From those reasons, the researcher used Guided Question technique i.e., giving questions before making a writing text. There werere three things that would be analyzed: 1) How is the implementation of Guided Question technique in teaching writing of recount text?, 2) How are the students’ compositions as the result of teaching writing recount text by using Guided Question technique?, 3) How are the students’ responses of the implementation of Guided Question technique in teaching writing of recount text?. Related to those questions, this study employed qualitative approach and the researcher used descriptive design. Moreover, the instruments were field note, observation checklist, students’ task, and interview. This research conducted three times observation in X-IPS 3 of SMAN 1 Mojosari in order to find out the implementation of Guided Question technique in teaching of recount text for senior high school students. The result of the observations showed that mostly the students’ compositions were in the level of good to average. In addition, the interview showed that most of the students gave positive responses. They agreed that this technique helped them in organizing their ideas. In summary, Guided Question Technique is appropriate technique in teaching writing recount text. Keyword: Writing, Recount text, Guided Question Technique